Electric and magnetic fields associated with the use of elecrical power in the workplaces in underdeveloped countries - Farag A. (2023)
It is a modern fact of life that whether humans at work, at home, or at school, are all exposed to low frequency electric and magnetic fields (EMFs) produced by the generation, transmission, and use of electricity. Some human health studies suggest that there may be links between exposure to EMFs and certain types of cancer, primarily leukaemia and brain cancer. Some scientists doubt that this apparent connection between EMF exposure and cancer is real, as it is difficult to explain biologically and due to the inconsistency of the research results. Most agree that more information and researches are needed to resolve the issue about whether or not EMFs affect human health. Many developed and industrialized countries have initiated national EMF research efforts and programs and important study results are expected in the next few years. This paper provides a thorough investigation and information about EMF exposure in the workplaces in some underdeveloped countries such as Egypt, Saudi Arabia and other Gulf Countries. The paper describes what researchers have learned about typical EMFs exposures in various work environments and identifies sources of EMFs in various industries and workplaces in those countries. This information should help designers, decision-makers, workers and employers understand the scientific basis of the concerns and the uncertainties about EMF exposure and set the standards for such equipment exposures.